We go farther together: practical steps towards conducting a collaborative autoethnographic study. Issue 2 (16th June 2022) - Ratnapalan, Savithiri; Haldane, Victoria
Abstract : ABSTRACT: Autoethnography is an underused qualitative research method in implementation science. Autoethnography can be used to reflect on and archive personal experiences, which can yield useful information to advance our knowledge. In particular, collaborative autoethnography is an important method towards providing greater insights on the experiences of multidisciplinary teams conducting research amidst complexity and intersectionality. In conducting a collaborative autoethnography, all authors are participants who narrate, analyze and theorize about their individual and or collective experiences. This article provides an overview of collaborative autoethnography for health research teams and implementation scientists embarking on autoethnographic studies.